Removal of phosphorus from synthetic wastewater using recycled concrete aggregates as a filter medium - ‪Adnan, Suraya Hani‬; Hamdan, ‪Rafidah; Yassin, N.I.M.; Roni, N. A. (UNIMAS, 2018)
These days, sustainability has become a primary concern as the large amount of natural resources are being used to produce materials such as concrete. Concrete from the construction industry constitutes the major proportion of construction waste. This could bring negative impact including depletion of natural resources, pollution, increasing landfill space, and high cost of waste disposal. All of these negative impacts are the sustainability issues that should be concentrated on. Hence, alternative methods have been introduced in order to reduce waste by recycling concrete waste. One of the alternative methods that can be used is by reusing recycled concrete aggregates (RCA) from discarded waste cubes. RCA can be used to produce new concrete but it will generally have a lower performance compared to normal concrete. Thus, the present study introduces an alternative method which is by reusing the RCA as a water filter medium to remove phosphorus from wastewater. Phosphorus is one of the inorganic compounds found in wastewater that can lead to environmental problems such as eutrophication. Based on previous studies, many types of materials with various chemical compositions have been used for phosphorus removal from wastewater. Therefore, this study demonstrates the ability of RCA as an alternative method for phosphorus removal from wastewater. In addition, three different factors have been considered in the removal of phosphorus namely, different initial concentration of phosphorus, different sizes of RCA and dosage of RCA used during the treatment process. Based on the experiments conducted, the lowest initial concentration of phosphorus of 10 mg/L, the smallest RCA size ranging between 0mm to 5mm and the highest RCA dosage of 50g resulted in the highest percentage of phosphorus removal in wastewater.